2000
DOI: 10.1103/physrevb.61.r13361
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis and spikes in the quantum Hall effect

Abstract: We observe sharp peaks and strong hysteresis in the electronic transport of a two-dimensional electron gas (2DEG) in the region of the integral quantum Hall effect. The peaks decay on time scales ranging from several minutes to more than an hour. Momentary grounding of some of the contacts can vastly modify the strength of the peaks. All these features disappear under application of a negative bias voltage to the backside of the specimen. We conclude, that a conduction channel parallel to the high mobility 2DE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
22
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 8 publications
9
22
1
Order By: Relevance
“…Also, keeping the Fermi energies of the layers equal as a function of sweeping magnetic field requires some charge transfer between the wells. There are, therefore, possibly interesting phenomena at high magnetic fields that can be explored in this system [22]. Third, the system has some remarkable properties even at zero or small magnetic fields.…”
mentioning
confidence: 96%
“…Also, keeping the Fermi energies of the layers equal as a function of sweeping magnetic field requires some charge transfer between the wells. There are, therefore, possibly interesting phenomena at high magnetic fields that can be explored in this system [22]. Third, the system has some remarkable properties even at zero or small magnetic fields.…”
mentioning
confidence: 96%
“…These hysteretic effects have been associated with a number of physical phenomena, including non-equilibrium charge distributions [3][4][5] , long-lived eddy currents [6][7][8][9] within the interior of the 2DES, first order phase transitions involving the electron spin [10][11][12][13][14][15] or pseudospin [16][17][18][19] degrees of freedom, and metastable orientations of the electron nematic phases at high Landau level occupancy 20 . In the majority of these experiments the behavior of the collective electron state was inferred from measurements of magnetoresistance, which was found to depend strongly on the sweep rate and direction of the magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [13] reported hysteresis in 2D electron systems with a parallel conducting layer. In their case, the parallel layer was a parasitic, low-mobility, doping layer at a distance of 75 to 95 nm away from the high-mobility 2D electrons.…”
mentioning
confidence: 99%